The social costs of underemployment : inadequate employment as disguised unemployment - Dooley, David; Prause, JoAnn, 1953- (Cambridge, UK ; New York, NY USA : Cambridge University Press, 2004)
Comparing the effects of unemployment and inadequate employment relative to adequate employment, this text studies their effects on self-esteem, alcohol abuse, depression, and birth weight. Using longitudinal methods, it measures controls for reverse causation (selection) and studies a large representative sample of Americans from their late teens in 1979, to their early 30's in the last decade of the twentieth century through stages of different business cycles. The results point to a rethinking of employment status as a continuum. --Publisher.
Preface -- 1. Disguised unemployment and changing forms of work -- 2. The social costs of unemployment -- 3. Data sources and methods -- 4. Reverse causation : findings on the selection hypothesis -- 5. Leaving school : self-esteem in an unwelcoming economy -- 6. Early adulthood : alcohol misuse and underemployment -- 7. Settling down : psychological depression and underemployment -- 8. Extending the employment continuum : well-being in welfare transitions -- 9. The next generation : underemployment and birthweight -- 10. Conclusions -- 11. New directions -- appendix A. Description of NLSY sample at selected survey years -- appendix B. Alcohol variable by survey year : NLSY79 -- References -- Name index -- Subject index.
Includes bibliographical references (pages 241-259) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Underemployment; Underemployment -- Health aspects; Underemployment -- Psychological aspects; Unemployment; Health status indicators; Unemployment; Socioeconomic Factors; Health Status Indicators; Unemployment -- statistics & numerical data; Unemployment -- psychology; Sous-emploi.; Sous-emploi -- Aspect sanitaire; Sous-emploi -- Aspect psychologique; Chômage.; Indicateurs de santé.; unemployment; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; Unemployment; Underemployment; Underemployment -- Psychological aspects; Unterbeschäftigung; Psychologie; Arbeid; Werkloosheid; Verborgen werkloosheid; Gezondheid; Gezondheidseffecten; Statistics; Statistics; Statistics; Statistiques